Video analysis of the deformation and effective mass of gymnastics landing mats - Pain, M. T. G.; Mills, C. L.; Yeadon, M. R. (Medicine & Science in Sports & Exercise, 2005)
Introduction: Landing mats that undergo large area deformation are now essential for the safe completion of landings in gymnastics. The aim of this study was to determine the effective mass, shock transmission time, and deformation characteristics of a mat during impacts using high-speed video and to improve the accuracy of measuring foot-mat contact forces during landing. For validation, the same variables need to be accurately assessed using accelerometer and force plate data.